2015
DOI: 10.18632/oncotarget.2730
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of N-terminal kinase like gene promotes tumorigenicity of hepatocellular carcinoma by regulating cell cycle progression and cell motility

Abstract: Amplification and overexpression of CHD1L is one of the most frequent genetic alterations in hepatocellular carcinoma (HCC). Here we found that one of CHD1L downstream targets, NTKL, was frequently upregulated in HCC, which was significantly correlated with vascular invasion (P = 0.012) and poor prognosis (P = 0.050) of HCC. ChIP assay demonstrated the binding of CHD1L to the promoter region of NTKL. QRT-PCR study showed that the expression of NTKL positively correlated with CHD1L expression in both clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Cell cycle dysregulation is a common feature of human cancers that leads to at least two hallmarks of cancer development, namely, uncontrolled cell proliferation and genomic and chromosomal instability. 1 , 2 , 3 It is well established that proper progression through the cell cycle is monitored by members of the cyclin-dependent kinase (CDK) family, whose activity is regulated by specific activators (cyclins) and inhibitors (Ink4 and Cip/Kip family members). 4 Constitutive CDK activation causes a significant change in protein phosphorylation and drives tumor cell cycle progression, which results in unscheduled cell proliferation and tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle dysregulation is a common feature of human cancers that leads to at least two hallmarks of cancer development, namely, uncontrolled cell proliferation and genomic and chromosomal instability. 1 , 2 , 3 It is well established that proper progression through the cell cycle is monitored by members of the cyclin-dependent kinase (CDK) family, whose activity is regulated by specific activators (cyclins) and inhibitors (Ink4 and Cip/Kip family members). 4 Constitutive CDK activation causes a significant change in protein phosphorylation and drives tumor cell cycle progression, which results in unscheduled cell proliferation and tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Activated FOXO3a disturbed the interaction between β-catenin and TCF and inhibited the expression of β-catenin/TCF target genes CyclinD1[ 24 ]. NTKL overexpression could accelerate the mitotic exit and chromosome segregation, which could promote G1/S transition by decreasing P53 and increasing CyclinD1 expressions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 27 ] Kazal-like domains proteoglycan 1 and N-terminal kinase like, as 2 of CHD1L targets, upregulated or activated by CHD1L, participated in tumorigenicity of HCC. [ 28 , 29 ] Additionally, a novel molecular pathway, CHD1L/TCTP/Cdc25C/Cdk1, was demonstrated to induce mitotic defects and chromosome missegregation in HCC development. [ 30 ] Researcher also found that CHD1L showed a strong oncogenic ability in CRC, the overexpression of which could promote tumor progression by promoting G1/S-phase cells and inhibiting apoptosis in CRC.…”
Section: Discussionmentioning
confidence: 99%